Potential of Liquid Probiotics Bacillus subtilis and Bacillus coagulans on Broiler Chicken Carcas Percentage and Business Analysis - Muhammad Ilyas Wahyudi; Maslichah Mafruchati; Sunaryo Hadi Warsito; Mohammad Sukmanadi; Sri Hidanah; Mohammad Anam Al-Arif (Jurnal Agro Veteriner, 2024)
The aim of this research was to find out liquid probiotic Bacillus subtilis and Bacillus coagulans as feed aditive to carcass percentage and economic analysis in broiler. This research used 24 broiler aged 20 day. P0 (control group) was given 2 ml of aquadest. P1, P2, and P3 were given liquid probiotic Bacillus subtilis and Bacillus coagulans with different dosage respectively (2 ml, 4 ml, and 6 ml). The sample of data was taken by weighing broiler manually. The data of carcass percentageanalyzed using one way Analysis of Variance (ANOVA) and if showed significant difference, continue by Duncan test as post-hoc test. The data of business analysis analyzed by descriptive. The result of this research was indicate that all doses 2 ml, 4 ml and 6 ml of liquid probiotic were significnat difference (p<0.05) in carcass percentage. The result of doses 4 ml of liquid probiotic was most higher than doses 2 ml and 6 ml in carcass percentage. Business analysis in this research gave effect in contribution margin and value > 1 of the revenue cost ratio which could be stated that the broiler business was feasible.